Future Planning and Development Direction for Al Ezaryya and Abu Dees Towns - Mohammad Anwar Hassan Al Khateeb (My University, 2003)
This study is based on the trends of the futuristic planning and development for Abudis and Al-izariyyah towns. This study is considered important for the following : - The Israeli policy in Jerusalem and the towns surrounding the city. - The rapid development in buildings and constructions which the area of the study discussed. - The shortage in branches and public services. Goals of the study could be mentioned as the following: 1- Studying the reality of the area at the constructional, social, population, economical and services level. 2- Studying the place relationship patterns between the study area and the cities surrounding it. 3- Defining the stages of the construction development. 4- Defining the most important problems at all levels, and defining the real which causes those problems. Finally, bringing on planning solutions according to the criterions and the available potentials A methodical approach was followed up based on major axels. It was represented in setting theoretical framework including concepts, models, literatures that will be used, and on which we can rely on in holding this study. Added to that the statistics and the studies which deals with the subject, then dealing and analyzing the information through using statistical and quantitative methods, as the statistical analyzing program, gravity law and some quantitative models. The study summarizes the following results: 1- The study area lacks for the necessary branches and services. 84.4% of the population don't have drainage network in their area. 2- the limitedness in the development and in extending buildings because of the Israeli planned policy. 3- The weakness of classification for the study area. Is it rural, countryside or suburb. 4- The absence of homogeneity between the citizens of the area. 5- The area is considered an attracting area to be populated. 6- The weak regional relationship with Jerusalem by time, especially after the Intifada of Al-Aqsa mosque in the year 2000, and other results.

This study is based on the trends of the futuristic planning and development for Abudis and Al-izariyyah towns. This study is considered important for the following : - The Israeli policy in Jerusalem and the towns surrounding the city. - The rapid development in buildings and constructions which the area of the study discussed. - The shortage in branches and public services. Goals of the study could be mentioned as the following: 1- Studying the reality of the area at the constructional, social, population, economical and services level. 2- Studying the place relationship patterns between the study area and the cities surrounding it. 3- Defining the stages of the construction development. 4- Defining the most important problems at all levels, and defining the real which causes those problems. Finally, bringing on planning solutions according to the criterions and the available potentials A methodical approach was followed up based on major axels. It was represented in setting theoretical framework including concepts, models, literatures that will be used, and on which we can rely on in holding this study. Added to that the statistics and the studies which deals with the subject, then dealing and analyzing the information through using statistical and quantitative methods, as the statistical analyzing program, gravity law and some quantitative models. The study summarizes the following results: 1- The study area lacks for the necessary branches and services. 84.4% of the population don't have drainage network in their area. 2- the limitedness in the development and in extending buildings because of the Israeli planned policy. 3- The weakness of classification for the study area. Is it rural, countryside or suburb. 4- The absence of homogeneity between the citizens of the area. 5- The area is considered an attracting area to be populated. 6- The weak regional relationship with Jerusalem by time, especially after the Intifada of Al-Aqsa mosque in the year 2000, and other results.
اتجاهات التخطيط والتطور المستقبلي لبلدتي العيزرية وأبو ديس